Strategi Pembentukan Karakter Religius Siswa melalui Program Keagamaan Rutin di SMA Islam Al-Ulum Terpadu Medan - Azizah, Ilma Septia; Zailani, Zailani (EL-EMIR Institute, 2025)
This study aims to analyze strategies for developing students’ religious character through routine religious programs at SMA Islam Al-Ulum Terpadu Medan. The research is grounded in the urgency of religious character education amid challenges of moral degradation, popular culture, and the penetration of digital technology. A qualitative case study design was employed. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, presentation, and conclusion drawing, with triangulation of sources to ensure validity. The findings reveal that the strategies for religious character formation are carried out in a structured, continuous, and collaborative manner. These strategies include teacher role modeling as uswah hasanah, habituation of worship practices such as the one day one verse program, sholat dhuha, morning dzikir, and congregational prayers, active student participation in religious leadership, evaluation of Qur’an memorization through weekly and annual tahfiz assessments, as well as the reinforcement of a religious culture through Islamic holidays and social activities. The study concludes that these strategies effectively enhance students’ religiosity, strengthen the role of teachers as role models, and foster a distinctive religious school culture. This model can serve as an implementable reference for other Islamic schools in nurturing a generation with Islamic character and integrity